PISA truth effects: the construction of low performance. Issue 3 (3rd May 2016) - Serder, Margareta; Ideland, Malin
Abstract : This article seeks to unpack the taken-for-granted notion of low performance, arguing that performance and competency are not a given categories; rather they are "objects-for-thought" that receive their discursive and material contours through a chain of translations. As suggested previously by Gorur, PISA is analyzed through the lens of Latourian Science and Technology Studies. The arguments in this article are based on an analysis of situations constructed to observe how performance is enacted in socio-material practice, as 15-year-old students collaboratively solve PISA scientific-literacy items. As background a text analysis, concerning how scientific literacy and performance are discursively constructed in various PISA materials, is reported. We suggest the notion of 'competency' be linked to the historical event of trying to start to detect it and argue that PISA results are products of the situated adjustments that are enacted by students and items created in the very moments of scientific measurement.